Digital piracy: a global, multidisciplinary account - Brown, Steven Caldwell; Holt, Thomas J. (Routledge studies in crime and society, 2018)
Digital Piracy : a global, multidisciplinary account : contextualising digital piracy / Thomas J. Holt and Steven Caldwell Brown -- The times they are a-changin : digital music value in transition from piracy to streaming / Hyojung Sun -- Digital piracy, new media, and Consumer Choice, Holly Tessler and Kenny Forbes -- Anti-piracy policies, online film circulation, and on-demand culture : the Italian context between formality and informality / Valentina Re -- The social and applied psychology of engagement in music piracy / Amanda Krause and Steven Caldwell Brown -- An examination of digital piracy behavior through the lens of cultural and non-cultural variables / Monika Kukar-Kinney, Irena Vida, and Mateja Kos Koklic -- Copyright infringement and cultural participation / Juan D. Montoro-Pons, Manuel Cuadrado-Garcia, and Migeul Puchades-Navarro -- Who cares if Taytay gets pay pay? shake it off : the apathy of the contemporary music consumer / Gary Sinclair -- Deliberating the information commons : a critical analysis of intellectual property and piracy / Kevin Steinmetz and Alexandra Pimentel --The criminality of digital piracy : is it a pathway more serious offending? / George Burruss and Cassandra Dodge -- Criminology's contribution to the study of digital piracy / Adam Bossler and Tyler Edwards -- Identifying paths forward in the study of piracy / Steven Caldwell Brown and Thomas J. Holt